Dynamics of land use land cover change and its effect on urban heat island in Halaba Kulito Town - Begonet Dale; Mihret Dananto; Bisrat Kifle (Heliyon)
Halaba Kulito Town in Ethiopia has experienced significant urbanization over the past three decades, leading to the conversion of natural land into built-up environments, causing environmental deterioration and impacting the local climate. This study set out to look at the dynamics of land use and cover change and how they have affected Halaba Kulito Town's Urban Heat Island during the previous thirty years. The analysis used the Landsat imagery (30 m × 30 m) of 1991, 2001, 2011, and 2021. The supervised classification approach was used to classify the images. The evaluation of classification accuracy was checked using a confusion error matrix. For the years 1991, 2001, 2011, and 2021, the LULC change classification accuracy evaluation showed results of 70.81 %, 81.3 %, 81 %, 91 %, and 0.71, 0.81, 0.81, and 0.89, respectively, for overall classification accuracy and kappa coefficient. In 2001, 2011, and 2021, the built-up increased by 23.6 %, 31.6 %, and 43.13 %, respectively. Over the first two decades, from 1991 to 2001 and 2001 to 2011, the quantity of land under cultivation increased by 15.7 % and 14.3 %, respectively, but dropped by 59.18 % from 2011 to 2021. Between 1991 and 2001, range land dropped by 33.3 %; nevertheless, in the next two decades, it expanded by 3.3 % and 83.2 %. The amount of bare land declined by 67.1 % between 2001 and 2011, although it increased by 38.8 % between 1991 and 2001 and 3.36 % between 2011 and 2021. In addition, wetland increased by 47.1 % and 191.95 % between 2011 and 2021 and between 1991 and 2001, respectively, while declining by 62 % between 2001 and 2011. Compared to the baseline 1991-year aerial coverage, built-up, range land, and wetland expanded by 132.9 %, 26.2 %, and 63.3 % over the previous thirty years, whereas bare land and cultivated land dropped by 46 % and 52.8 %, respectively. The mean urban heat island (UHI) for 1991, 2001, 2011, and 2021 incorporating seasonal influence was 0.003, 0.002, 0.005, and 0.00, respectively. This is because the intensity of the UHI is correlated with changes in land use and land cover (LULC). In contrast, the lowest UHI dropped by 35.3 % in 2021 compared to the value in 1991, while the maximum UHI increased by 18.6 % from its 1991 level. In comparison to 1991, the mean intensity of UHI increased by 106.21 % and 120.4 %, respectively, in 2011 and 2021, whereas it declined by 20.67 % in 2001. The findings of this study offer decision makers with scientifically proven knowledge about land use and its implications for the urban heat island effect. It will serve as a guideline for developing and implementing integrated land use management to produce climate resilient cities and create livable urban environments for citizens.